Communicating strategically in English as a lingua franca : a corpus driven investigation - Jafari, Janin (London ; New York : Routledge, 2020)
"There have been noticeable demographic changes made in the use of English around the world recently. English as a medium of communication is now the contact language of native speakers from many diverse speech communities who interact with each other in multilingual contexts. The use of English as a lingua franca (ELF) and its implications has become a hot topic in Applied Linguistics and English Studies. Communicating Strategically in English as a Lingua Franca reflects the growing interest in achieving communicative effectiveness in ELF situations and provides a comprehensive account of recent empirical findings in the field of English as a lingua franca (ELF). It analyzes and interprets the authors own large corpus of naturally occurring spoken interactions and focuses on identifying innovative employments in the communicative strategies and pragmatics of speakers involved in ELF interactions. In doing so, it makes a considerable contribution to the growing field of empirical studies in ELF. This book explores the usage of pragmatic strategies and highlights their significant role in communicative effectiveness in ELF interactions. In showing the processes of classifying communication strategies involved in the identification of newly observed communication strategies, this book will be of great interest to English linguists applied linguists, graduate and undergraduate students of English, ELT material developer and teachers of English"--
The spread of English in a global world -- English as a global language -- The usage of communication strategies -- Investigating ELF interaction -- Identifying and categorizing communication strategies in ELF -- Achieving mutual understanding in ELF: focus on communication strategies -- Affecting the choice of CSs: A focus on contextual factors -- The theoretical and practical implications of ELF -- Concluding remarks.
OCLC-licensed vendor bibliographic record.
Keywords: English language -- Globalization; English language -- Variation -- English-speaking countries; English language -- Variation -- Foreign countries; Lingua francas; Corpora (Linguistics); LANGUAGE ARTS & DISCIPLINES / Communication; LANGUAGE ARTS & DISCIPLINES / Rhetoric